1989
DOI: 10.1111/j.1365-2362.1989.tb00222.x
|View full text |Cite
|
Sign up to set email alerts
|

Mobilizable lead in patients with chronic renal failure

Abstract: Blood lead (Pb) and urinary Pb before and after i.v. infusion of 1 g of Na2Ca EDTA were determined (atomic absorption) in 46 control subjects and 91 patients with various stages of renal failure (median serum creatinine 2.5 mg dl-1). Under baseline conditions, patients with renal failure had higher blood Pb levels (112 ng ml-1, range 44-272 vs. 76; 36-187 in controls; P less than 0.001) and lower urinary Pb (16.2 nmol 24 h-1 1.73 m-2, 4.86-66.8 vs. 33; 11-91 in controls; P = 0.001). The increment in urinary Pb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

1990
1990
2013
2013

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(7 citation statements)
references
References 22 publications
0
7
0
Order By: Relevance
“…It would be useless to compare only healthy controls and 'CRF patients' as the latter would represent a mixture of patients with CRF of known and unknown aetiologies, all of them with or without overt Pb exposure. With the study designs used by a number of authors [4,5,[22][23][24] it is only possible to state that some CRF patients have high levels of Pb burden, but it is impossible to clearly discern what proportion of CRF is a consequence of the excessive Pb burden.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…It would be useless to compare only healthy controls and 'CRF patients' as the latter would represent a mixture of patients with CRF of known and unknown aetiologies, all of them with or without overt Pb exposure. With the study designs used by a number of authors [4,5,[22][23][24] it is only possible to state that some CRF patients have high levels of Pb burden, but it is impossible to clearly discern what proportion of CRF is a consequence of the excessive Pb burden.…”
Section: Discussionmentioning
confidence: 99%
“…Its long-term effects as an environmental pollutant and poison have only become a matter of concern in the last few years and is thought to be a world-wide risk for all populations. The idea of Pb-associated renal disease is an ancient concept [1], but still some degree of controversy persists even today as to the role of chronic Pb intoxication as a cause of chronic renal failure (CRF) [2][3][4][5]. Available reports, based in most cases on occupationally exposed workers [6][7][8][9][10][11][12][13], generally involve Pb as a cause of CRF, but still some do not find such a relationship [14,15].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Finally, low-level exposure to Pb has recently been discussed in the genesis of hypertension [35,36]. This concept is based upon the finding that a significant correlation is noted between blood Pb levels and arterial blood pressure in the general population [37,38] and that Pb in several animal studies increased blood pressure and pressor responsiveness [39].…”
Section: Discussionmentioning
confidence: 99%
“…The transfer coefficient for blood to urine, which was estimated by the process described above, is the blood lead mass divided by the rate at which lead is eliminated from the blood through the urine. A literature review revealed seventeen adult studies for evaluating this coefficient (46,51,(76)(77)(78)(79)(80)(81)(82)(83)(84)(85)(86)(87)(88)(89)(90). The adult value was allometrically scaled to children 0 to 84 months of age, based on proportionality between the blood volume and glomerular filtration rate for that age group.…”
Section: Growth Equationsmentioning
confidence: 99%